Phosphorylated alpha-synuclein distribution in the colonic enteric nervous system of patients with diverticular disease - François Cossais; Marie Christin Hörnke; Katja Schröder; Ralph Lucius; Martina Böttner; Jan-Hendrik Egberts; Florian Richter; Thilo Wedel (IBRO Neuroscience Reports)
Background: Phosphorylated alpha-synuclein (P-aSyn) is a biomarker for Parkinson’s disease (PD), with potential relevance in intestinal inflammatory disorders. Objectives: This study examines the distribution of P-aSyn in colonic tissues of patients with diverticular disease (DD) compared to age-matched controls. Methods: P-aSyn distribution was analyzed in colon samples of 45 patients with diverticulitis (D-itis), 12 with diverticulosis (D-osis), and 30 controls via immunohistochemistry. Results: P-aSyn immunoreactivity was found along enteric neurons of the myenteric and submucosal plexus in 93.1 % of participants, with similar distribution across D-itis, D-osis, and controls. Elevated reactivity appeared in 16.7 % of D-osis, 19.6 % of D-itis, and 30.0 % of controls. Conclusion: P-aSyn presence in colonic tissue did not significantly differ between DD patients and controls, suggesting that DD-related inflammation does not notably affect P-aSyn expression. Further research is warranted to explore aSyn roles within the enteric nervous system in intestinal inflammatory disorders and their relation with neurodegenerative diseases.